1976
DOI: 10.2165/00003088-197601020-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics in Neonates

Abstract: Recent concern over toxic effects of drugs in newborns, infants and children have stressed the need for better knowledge of drug kinetics during development. The present review focuses on the available data on clinical pharmacokientics in the neonate. Despite the lack of systematic approaches on drug disposition during the first month of life, the body of data currently available indicates profound differences in drug disposition between neonates and older infants, children and adults. In terms of physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(61 citation statements)
references
References 93 publications
2
56
0
3
Order By: Relevance
“…The significant influence of both weight and postnatal age on CL agreed with the population study of Moore et al [6] and aligns with the fact that these demographic factors are closely related to the degree of development of major drug clearance organs such as the liver and kidneys [13]. In contrast to another report [14], postnatal age was better than the number of theophylline treatment days, or postconceptional age in modelling clearance.…”
Section: Discussionsupporting
confidence: 88%
“…The significant influence of both weight and postnatal age on CL agreed with the population study of Moore et al [6] and aligns with the fact that these demographic factors are closely related to the degree of development of major drug clearance organs such as the liver and kidneys [13]. In contrast to another report [14], postnatal age was better than the number of theophylline treatment days, or postconceptional age in modelling clearance.…”
Section: Discussionsupporting
confidence: 88%
“…The levels of SCE-2787 and ceftazidime in plasma in young dogs were lower than those in mature dogs. It has been shown that the volume of extracellular fluids per kilogram of body weight in young animals and humans is larger than that in mature animals and humans: the V of ,B-lactam antibiotics at steady state in the infants is generally greater than that in the adults (5,9). This may be due to the fact that the CLp and Vin young dogs were larger than those in mature dogs ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The area of pediatric pharmacokinetics has blossomed since the 1970s, when advances in the development of sensitive and specific drug assays began. Pharmacokinetic parameters such as clearance (CL), volume of distribution (V) and half-life (t112) have been described for many therapeutic agents used in the newborn and young infant (1)(2)(3)(4)(5)(6) and numerous reviews are devoted to this subject (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, quantitation of clinical effects and pharmacodynamic response as modified by development and disease are areas that have lagged behind description of pharmacokinetics in this age group (10).…”
Section: Introductionmentioning
confidence: 99%